The Influence of Entrepreneurial Cognition on Business Model Innovation: A Hybrid Method Based on Multiple Regressions and Machine Learning - Zhou, Jian; Yang, Jian; Sun, Hehe; Liu, Yang; Liu, Xiao (Frontiers in Psychology, 2021)
How to achieve business model innovation has always been a focus topic in the field of entrepreneurship. Based on cognitive theory, this study takes new ventures as the research object to build a theoretical model to explore the impact of entrepreneurial cognition on business model innovation choice, its intermediary mechanism and boundary conditions. We test our framework with a sample of 242 questionnaires, the empirical research results show that entrepreneurial configuration cognition, willing cognition and ability cognition indirectly affect the business model innovation of new ventures. Strategic sensitivity mediated the relationship between entrepreneurial cognition and business model innovation, knowledge diversity positively moderates the relationship between strategic sensitivity and business model innovation. Machine learning algorithm research has found three prediction models for business model innovation of new ventures. By constructing a theoretical analysis framework of business model innovation from the perspective of cognition, the results deepen the relevant research on business model innovation of new ventures, clarify the source of unique characteristics and capabilities of entrepreneurs, provide a new research perspective for analyzing the impact mechanism of entrepreneurial cognition on business model innovation, enrich the research results in the field of "situation-cognition-behavior", and further clarify the important role of knowledge for the development of new ventures.